Development and Validation of Reversed Phase-High-Performance Liquid Chromatography, Dissolution Method for Simultaneous Estimation of Aminocaproic Acid in Pharmaceutical Dosage Forms: Development and Validation of Reversed Phase-High-Performance Liquid Chromatography, Dissolution Method for Simultaneous Estimation of Aminocaproic Acid in Pharmaceutical Dosage Forms - Patel, Miral (International Journal of Pharmaceutical & Biological Archive, 2020)
A simple, accurate, precise, and robust in vitro methods developed and validated for measurement of drug release in Aminocaproic Acid tablets. High-performance liquid chromatography (HPLC) method for quantification of drug in dissolution samples of Aminocaproic Acid tablet is developed and validated. 0.1 N Hydrochloric acid is used as dissolution medium and Basket (USP-I) as apparatus at 100 rpm. The sample was withdrawn after 60 min. The developed HPLC method was used for quantitative estimation of drug release in dissolution samples of Aminocaproic Acid tablet. Chromatogram was run through Inertsil ODS 3V, (250 Ã— 4.6 mm), 5 Î¼m. Mobile phase containing buffer solution and methanol in the pumped through column at a flow rate of 1 ml/min. Buffer used in this method was 13.3 g sodium dihydrogen phosphate monohydrate, 500 mg of Heptane-1-sulfonic acid sodium salt, and 1.0 mL of Triethylamine buffer with pH 2.20 adjusted by orthophosphoric acid. Optimized wavelength for Aminocaproic acid was 210 nm. Retention time of Aminocaproic acid was found about 4.0 min; linearity range was 132.605 Î¼g/mlâ€“828.787 Î¼g/ml. The new method was evaluated according to ICH guideline and as far as validation results are concern correlation coefficient value was 0.9999 for the very compound, percentage recovery 100.0%, repeatability results relative standard deviation 0.9 for Aminocaproic acid. The developed HPLC method was found to be a simple and rapid one for regular analysis in professional laboratory.